2010
DOI: 10.1007/s11145-010-9244-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of reading skills for kindergartners and first grade students in Spanish: a longitudinal study

Abstract: This study investigated predictors of word reading and reading comprehension skills using longitudinal data from Spanish-speaking kindergartners (N = 163) and first grade students (N = 305) from high SES families in Chile. Individual differences in letter-naming fluency and phonemic segmentation fluency, but not vocabulary, were positive predictors of word reading, over time, for kindergartners. Furthermore, kindergartners with higher letter-naming fluency and phonemic segmentation fluency had a faster rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 55 publications
4
38
0
13
Order By: Relevance
“…These skills can be measured in kindergarten or early on in fi rst grade and include phonological abilities, rapid automatized naming (RAN), letter knowledge, grammatical skills, and vocabulary (Badian, 1995 ;Muter, Hulme, Snowling, & Stevenson, 2004 ). Our fi ndings among Hebrew speaking children replicate and expand several studies that have identifi ed additional cognitive skills related to word reading, such as memory, executive skills, speed of processing, and other aspects of general ability (Brunswick et al, 2012 ;Kim & Pallante, 2012 ;Lervag, Braten, & Hulme, 2009 ;Muter et al, 2004 ). In the discussion we address the importance of including multiple measures to identify poor word readers.…”
Section: Discussionsupporting
confidence: 77%
“…These skills can be measured in kindergarten or early on in fi rst grade and include phonological abilities, rapid automatized naming (RAN), letter knowledge, grammatical skills, and vocabulary (Badian, 1995 ;Muter, Hulme, Snowling, & Stevenson, 2004 ). Our fi ndings among Hebrew speaking children replicate and expand several studies that have identifi ed additional cognitive skills related to word reading, such as memory, executive skills, speed of processing, and other aspects of general ability (Brunswick et al, 2012 ;Kim & Pallante, 2012 ;Lervag, Braten, & Hulme, 2009 ;Muter et al, 2004 ). In the discussion we address the importance of including multiple measures to identify poor word readers.…”
Section: Discussionsupporting
confidence: 77%
“…The interaction of grade level and student condition showed that LC was significant while the interaction of the three variables together showed WD was significant. According to Kim & Pallante (2012), decoding can be word reading (or word recognition) and/or phonological decoding (e.g., non-word reading). In the current study we relied on the second type.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we relied on the second type. Phonological coding depends more on the grapheme-phoneme correspondence knowledge whereas word reading would draw on semantic and orthographic processes (Kim & Pallante, 2012). Phonological decoding fluency (i.e., nonsense word fluency) has been shown to be related to reading comprehension in a few studies with English-speaking children (Fien et al, 2008;cited in Kim & Pallante, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…La primera referencia en español a la CSL es de Alegría (2006), que la denomina "modelo simple de lectura", pero hasta 2012 no se encuentran los primeros estudios que intentan analizar la utilidad de este modelo para explicar la comprensión lectora en hablantes nativos de español (Infante, Coloma y Himmel. 2012;Kim y Pallante, 2012).…”
Section: Introductionunclassified
“…La utilidad de la CSL para explicar la comprensión lectora de hablantes monolingües de español ha sido investigada con alumnos chilenos (Infante et al, 2012;Kim y Pallante, 2012), españoles (Mesa, Melgarejo y Saldaño, 2013) y peruanos (Morales, Verhoeven y van Leeuwe, 2008, 2011Tapia, Aguado y Ripoll, 2016).…”
Section: Introductionunclassified